Physical fitness index of elderly people practicing physical activity in a project in the south zone of Aracaju – Sergipe - Figueiredo, Delson Lustosa de (2020)
Introduction: Aging is a physiological process that occurs in all living organisms with loss of cellular functions, which consequently decreases the chances of survival. Physical activity may not present a "fountain of youth," but most evidence shows that this regularly practiced retards the decline in the aging process. Objective: to identify the level of physical conditioning in the elderly who regularly attend a social project located in the South Zone of the city of Aracaju - SE. Methods: A descriptive character field survey was carried out. The sample consisted of elderly people from the Count with us project in the city of Aracaju-Se. Data were analyzed and classified using the Quartile statistical method through Excel 2010. To evaluate the physical conditioning of the elderly, the protocol of the Latin American Human Development Group for Maturity-GDLAM was used. Results: According to the results obtained, the majority was classified as insufficient, which can be explained by the characteristics of the physical activities proposed for these elderly people. Conclusion: It was concluded that, even when practicing physical exercises regularly, the elderly who participated in the sampling did not present satisfactory physical conditioning.